The The Analysis of PNM Mekar Syariah Financing Practices from the Perspective of Islamic Law in West Kalimantan - Basri, M; Hasani, Ahmad (FEBI UIN Sunan Kalijaga, 2024)
This study aims to evaluate the practice of lending money implemented by PT Permodalan Nasional Madani (PNM) Mekar Syariah in West Kalimantan, from the perspective of Islamic law. The phenomenon of capital needs for micro and small businesses is an important background for the birth of this Islamic financing institution. This study uses a qualitative approach with a field research method. Data were obtained through in-depth interviews, observations, and documentation which were then analyzed descriptively. The results of the study indicate that lending practices at PNM Mekar Syariah contain elements of Islamic financing contracts, but there are still several aspects that need to be adjusted to be fully in line with the principles of muamalah in Islam. This study recommends strengthening sharia supervision and ongoing guidance for customers to improve compliance with sharia values.